2021
DOI: 10.1080/08164622.2021.1971048
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and clinical features of conjunctival tumours at a tertiary care centre

Abstract: Supplementary Table 1. Distribution of 410 conjunctival tumors based on age groups and gender Category and diagnosis ≤20 years old Total (%), male (%), female (%) >20-40 years old Total (%), male (%), female (%) >40-60 years old Total (%), male (%), female (%) >60-80 years old Total (%), male (%), female (%)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
2
1
Order By: Relevance
“…African women have increased risk probably due to their higher prevalence of HIV and HPV infections (5). This result contrasts many studies that reported a higher male prevalence (19), (32), (30). Higher incidence of OSSN in male gender is associated with increased exposure to ultraviolet rays during outdoor work (33), however may also be attributed to racial background, with males predominating in Caucasians (34) (32).…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…African women have increased risk probably due to their higher prevalence of HIV and HPV infections (5). This result contrasts many studies that reported a higher male prevalence (19), (32), (30). Higher incidence of OSSN in male gender is associated with increased exposure to ultraviolet rays during outdoor work (33), however may also be attributed to racial background, with males predominating in Caucasians (34) (32).…”
Section: Discussioncontrasting
confidence: 56%
“…Different findings have been reported in Australia (68.9 years) (27), in UK (71 years) (28), in Taiwan (63.4 years) (29). and in Turkey (63.7 years) (30). This elderly mean age is due to the fact it has been reported that these places have a reduced exposure to UV light as most of the work is indoors, and have reduced level of HIV and HPV exposure.…”
Section: Discussionmentioning
confidence: 87%
“…Many studies have been conducted worldwide to describe the pattern of ocular tumor at national level 11 , 12 or at local level. 13 , 14 This research has succeeded in mapping of ocular cancer in the studied countries in term of incidence, gender differences, pathology, and natural history. In this research we conducted an examination of a substantial group of patients affected by ocular neoplasms within the Saudi population.…”
Section: Discussionmentioning
confidence: 99%